2015
DOI: 10.1074/jbc.m115.638320
|View full text |Cite
|
Sign up to set email alerts
|

The Radical S-Adenosyl-l-methionine Enzyme QhpD Catalyzes Sequential Formation of Intra-protein Sulfur-to-Methylene Carbon Thioether Bonds

Abstract: Background:The small subunit of quinohemoprotein amine dehydrogenase contains three Cys-to-Asp/Glu thioether bonds. Results:The radical S-adenosyl-L-methionine (SAM) enzyme QhpD catalyzes the single-turnover reaction of thioether bond formation in the protein substrate. Conclusion:The thioether bond formation by QhpD proceeds sequentially in an N-to C-terminal direction of the polypeptide. Significance: Our findings uncover another challenging reaction of radical SAM superfamily of enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 57 publications
5
66
0
Order By: Relevance
“…While there are reports of rSAM enzymes that install thioether linkages within protein substrates (e.g. QhpD acting on QhpC), 46 these are not considered RiPPs; thus, they will not be mentioned further.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…While there are reports of rSAM enzymes that install thioether linkages within protein substrates (e.g. QhpD acting on QhpC), 46 these are not considered RiPPs; thus, they will not be mentioned further.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…21,35,46,47 Since the characterization of these three enzymes, additional members of the RS superfamily, including QhpD, were observed to contain a Cys rich C-terminal domain that binds auxiliary [4Fe-4S] clusters. 38 BLAST search of Tte1186 revealed that it was homologous to both anSME and AlbA, suggesting that it contains the C-terminal SPASM domain. Both the bioinformatic analysis of Tte1186 and the excess Fe and S observed in both the wild-type and ΔRC variant discussed above suggested that Tte1186, by analogy to PqqE, AlbA, QhpD, and anSME, contains at least one auxiliary cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Thioether crosslinks have been observed previously in the maturation of subtilosin A, sporulation killing factor, thurincin H, and the γ subunit of quinohemoprotein amine dehydrogenase. 35,36,37,38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting alkyl radical forms a bond with a thiol of a nearby cysteine resulting in a cyclized peptide. Interestingly, most members of this group (AlbA, QhpD, ThnB, CteB, and SkfB) have been found to carry out multiple modifications on the same peptide, distinguishing them from the rest of the enzymes in Table 1, which modify only a single site in their substrates (33)(34)(35)(36)(37). In addition, the diverse physiological functions for the products of these RS enzymes, which include antibiotics (e.g.…”
Section: Carbon-carbon Bond Creation: Pqqe Strb and Mftcmentioning
confidence: 99%